Re: Polymorphisms Associated With Circulating Sex Hormone Levels in Postmenopausal Women - De Castro, Francisco; Moron, Francisco J.; Montoro, Luis; Galan, Jose J.; Real, Luis M.; Ruiz, Agustin (JNCI : Journal of the National Cancer Institute, 2005)
in the risk of breast cancer due to anTable 1. CYP 19 SNP rs10046 genotype distributions in pre- and postmenopausal breast cancer case patients and control subjects and breast cancer risk.[H11569]SNP rs10046 genotypeMenopausal statustt tc ccPPremenopausal women, nCase patients (n.notdefH11005 1407) 408 674 325